2018
DOI: 10.1038/s41598-018-33121-7
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity at 38 K at an electrochemical interface between an ionic liquid and FeSe0.8Te0.2 on various substrates

Abstract: Superconducting FeSe0.8Te0.2 thin films on SrTiO3, LaAlO3 and CaF2 substrates were electrochemically etched in an ionic liquid, DEME-TFSI, electrolyte with a gate bias of 5 V. Superconductivity at 38 K was observed on all substrates after the etching of films with a thickness greater than 30 nm, despite the different Tc values of 8 K, 12 K and 19 K observed before etching on SrTiO3, LaAlO3 and CaF2 substrates, respectively. Tc returned to its original value with the removal of the gate bias. The observation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 32 publications
(56 reference statements)
5
46
0
1
Order By: Relevance
“…In addition, O and Fe are detected in the top few nanometers of both samples without Se or Te elements, which hints at the probable existence of an Fe-oxide (FeO x ) layer above FeTe (not shown here). Similar oxidized Fe layers were also reported by Kouno et al [60] in their Fe(Se 0.8 Te 0.2 )/CaF 2 thin films.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, O and Fe are detected in the top few nanometers of both samples without Se or Te elements, which hints at the probable existence of an Fe-oxide (FeO x ) layer above FeTe (not shown here). Similar oxidized Fe layers were also reported by Kouno et al [60] in their Fe(Se 0.8 Te 0.2 )/CaF 2 thin films.…”
Section: Resultssupporting
confidence: 89%
“…Despite the various viewpoints, the intrinsic reason for the suppression of superconductivity in undoped ultrathin Fe-Ch films still remains elusive, which is preventing the discovery of HTS in this system. A very recent work published by Kouno et al [60] reported a T c at 38 K in an Fe(Se 0.8 Te 0.2 ) thin film on CaF 2 substrate. Similar to the top-down approach used by Shiogai [45], they focused on the interface between the Fe(Se 0.8 Te 0.2 ) layer and the ionic liquid electrolyte.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results indicate that an in situ process without exposure to air [40] is necessary for electric-field-induced superconductivity in FeSe EDLTs if an electrochemically etching process [34,38,39] is not employed. as-grown film and film exposed to air for 60 min are shown for comparison.…”
Section: Discussionmentioning
confidence: 95%
“…Another type of T c enhancement of FeSe has been reported by employing electric double-layer transistor (EDLT) configurations with ionic liquid as a gate dielectric material [34][35][36][37][38][39]. In these recent reports, the EDLT configuration serves two roles: it allows electrostatic doping of high-density carriers to the EDLT channels [35][36][37], and electrochemical etching of the EDLT channels under relatively high gate bias (e.g., ≥ 5 V) and at high temperature (close to room temperature) is applied to control the channel thickness and electrical properties [34,38,39]. Both of these factors contribute to achieving a high T c of approximately 40 K, which is close to that for the above cases of high pressure and chemical doping/intercalation.…”
Section: Introductionmentioning
confidence: 99%